Design of Temperature and Humidity Control System for Cocoa Bean Dryer Using Fuzzy Mamdani Method - Taufan Taufan Putra ananta; Chika Hayya Sabillah; Muhammad Faiz Assariy; Daffa Zulqisthi; Mariati; Putri Nurhaliza Candra; Audrey Anastasia Silaen; Febrina Disa Cinta Prasetyo; Windy Fadhilah Aprilia; Alifvia Nabila Cesarina Subekti; Mrr Lukie Trianawati (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
This research aims to develop a fuzzy logic control system for optimizing temperature and humidity during cocoa bean fermentation. The study employs a literature review method and data analysis using MATLAB. A Mamdani-type fuzzy inference system is designed to control the temperature and humidity of a cocoa bean dryer. Input variables include temperature (0-65°C) and humidity (0-100%), while output variables are heater and fan settings. The system's performance is evaluated using a case study, demonstrating its ability to adjust heater and fan operations based on environmental conditions. Results show that for an input of 65°C temperature and 50% humidity, the system recommends turning off the heater (membership value 79.8) and running the fan at high speed (membership value 84.7). This fuzzy logic approach offers a promising solution for maintaining optimal conditions during cocoa bean fermentation, potentially improving the quality and consistency of the final product. Keywords: cocoa fermentation, fuzzy logic control, temperature regulation